Deep Learning based Vehicle Detection in Aerial Imagery - Wilko Sommer, Lars (Karlsruher Schriften zur Anthropomatik, 2022)
This book proposes a novel deep learning based detection method, focusing on vehicle detection in aerial imagery recorded in top view. The base detection framework is extended by two novel components to improve the detection accuracy by enhancing the contextual and semantical content of the employed feature representation. To reduce the inference time, a lightweight CNN architecture is proposed as base architecture and a novel module that restricts the search area is introduced.